Ceramides as a hypothetical molecular link between high-fat diet and immune dysregulation in rheumatic diseases: a narrative review - Pysiewicz, Mateusz (Quality in Sport, 2026)
One of the components of the Western diet is saturated fatty acids (SFA). Their excessive consumption is associated with obesity and atherosclerosis, but they also appear to be related to immunity and rheumatic diseases. Ceramides are bioactive sphingolipids that have recently attracted growing scientific interest, as their role as a potential link between high-fat diet and rheumatic diseases is investigated. Ceramides are predominantly precursors of sphingolipids, which are basic components of cell membranes. They have also immunomodulatory functions, but their biological functions are context-dependent and are determined by pathway of their biosynthesis, the type of cell, and presence of cytokines. Experimental studies suggest that ceramides synthesized in response to excessive amounts of SFA in the diet may promote pro-inflammatory responses, including M1 macrophage polarisation, activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway, activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, Th17 polarisation of naïve CD4+ T cells, and production of pro-inflammatory cytokines. However, human data remain limited and heterogeneous, and it is unclear if ceramides function as drivers or biomarkers of immune activation. This review critically evaluates data from animal models and in vitro studies and summarizes data from human studies. It discusses pathways of ceramide biosynthesis, their immunological role, attempts to determine their role in rheumatic diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and psoriasis and evaluates their potential as biomarkers and potential therapeutic targets in these diseases.